(untitled) (Ciudades, 2017)
From the start of the 19th century and through to the middle of the 20th century, the increase in cases of tuberculosis, together with the development of different experimental therapies applied to cure this disease, gave rise to the appearance of very different types of sanatoria and tertiary complexes for health, called “cities of health”. The “sanatoria cities” German-Swiss, around of therapies based on climate, rest and pure air; the “rehabilitation colonies” for tuberculosis sufferers, employing work-based therapies; or the immense sanatoria of the middle of the 20th century, similar to the new constructions of the “modern cities”, are three examples of them. The sanatorium and the “cities of the health” are still valid referents to combat the problems of physical and psychological health that actually exist in the city.